Is There a Gender Wage Gap in Online Labor Markets? Evidence from Over 250,000 Projects and 2.5 Million Wage Bill Proposals - Estrella Gomez-Herrera; Frank Müller-Langer (Center for Economic Studies and ifo Institute (CESifo), 2019)
We explore whether there is a gender wage gap in one of the largest EU online labor markets, PeoplePerHour. Our unique dataset consists of 257,111 digitally tradeable tasks of 55,824 hiring employers from 188 countries and 65,010 workers from 173 countries that made more than 2.5 million wage bill proposals in the competition for contracts. Our data allows us to track the complete hiring process from the employers' design of proposed contracts to the competition among workers and the final agreement between employers and successful candidates. Using Heckman and OLS estimation methods we provide empirical evidence for a statistically significant 4% gender wage gap among workers, at the project level. We also find that female workers propose lower wage bills and are more likely to win the competition for contracts. Once we include workers' wage bill proposals in the regressions, the gender wage gap virtually disappears, i.e., it is statistically insignificant and very small in magnitude (0.3%). Our results also suggest that female workers' higher winning probabilities associated with lower wage bill proposals lead to higher expected revenues overall. We provide empirical evidence for heterogeneity of the gender wage gap in some of the job categories, all job difficulty levels and some of the worker countries. Finally, for some subsamples we find a statistically significant but very small “reverse” gender wage gap.
Keywords: D40; J40; 330; gender wage gap; online labor markets; digitally performable projects